Differences in salivary acidity before and after consumption of sugary drinks in children of Ra Hudallah Kujangsari Village, Langensari Subdistrict, Banjar City: Perbedaan derajat keasaman saliva sebelum dan sesudah konsumsi minuman manis pada anak-anak Ra Hudallah Desa Kujangsari Kecamatan Langensari Kota Banjar - Mellinia, Patricia Octaviane; Zalzamitha, Tifanny; Posumah, Gabriela Lestari Natalya; Sinaga, Nadya Atalia; Setiawan, Ignatius; Laksmi, Primarizka Iswara; Sugiaman, Vinna Kurniawati (Makassar Dental Journal PDGI Makassar, 2024)
This study aims to determine the effect of sugary drinks on the pH value of saliva in children, is an analytical observation with expe-rimental methods regarding the relationship of sugary drinks to the pH value of saliva measured using a pH meter. The research was conducted at RA Hudallah Kujangsari Village, Langensari Subdistrict, Banjar City. The results showed that before drinking sugary drinks, the majority of children had a normal pH category (64%), while after drinking sugary drinks, the pH state changed to be more acidic (70%) and only 22% had a normal pH category. It was concluded that after drinking sugary drinks, 78% expe-rienced a significant decrease in salivary pH, the rest had a normal pH.